2013
DOI: 10.1177/2047487313502447
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced ischemic preconditioning detected by sequential exercise stress tests: A meta-analysis

Abstract: Exercise-induced ischemic preconditioning (IPC) can be assessed with the second exercise stress test during sequential testing. Exercise-induced IPC is defined as the time to 1 mm ST segment depression (STD), the rate-pressure product (RPP) at 1 mm STD, the maximal ST depression and the rate-pressure product at peak exercise. The purpose of this meta-analysis is to validate the parameters used to assess exercise-induced IPC in the scientific community. A literature search was performed using electronic databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…A meta-analysis, based on 34 studies and 1,053 patients, reported a significantly later onset of ST depression (91 s) and a decrease in peak ST depression (-0.38 mm) on the second exercise stress test during sequential testing. 25 This supports the ability of exercise to induce immediate attenuation of cardiac ischemia. Pre-clinical work found that warm-up angina requires a preceding period of ischemia, 26 which in turn activates pathways that protect the myocardium against ischemia.…”
Section: Does Exercise Acutely Attenuate Cardiac Ischemia In Patients?supporting
confidence: 54%
“…A meta-analysis, based on 34 studies and 1,053 patients, reported a significantly later onset of ST depression (91 s) and a decrease in peak ST depression (-0.38 mm) on the second exercise stress test during sequential testing. 25 This supports the ability of exercise to induce immediate attenuation of cardiac ischemia. Pre-clinical work found that warm-up angina requires a preceding period of ischemia, 26 which in turn activates pathways that protect the myocardium against ischemia.…”
Section: Does Exercise Acutely Attenuate Cardiac Ischemia In Patients?supporting
confidence: 54%
“…16 Preconditioning effects of an exercise bout has also been shown previously on cardiac function in patients with coronary artery disease. 17 Early reports have raised concerns about the application of repeated IPC, suggesting repeated protocols may negate vascular protection. 18 Nevertheless, we found FMD was enhanced after 2-weeks (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Tomai et al 15 recorded that the effect of the warm-up phenomenon completely disappears in 2 hours and the effects were positive if the time between exercise stress tests was 10 minutes. 10 Beyond those timelines, the effects of preconditioning fade to baseline results. In brief, the FWOP can be assessed when sequential stress testing is separated by 10 to 60 minutes and 24 ± 2 hours for the SWOP.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…12 The initial transient ischemia generates molecules such as nitric oxide, adenosine, and reactive oxygen species leading to de novo (the synthesis of complex molecules from simple molecules) cardioprotective proteins, such as nitric oxide synthase, cyclo-oxygenase-2, and superoxide dismutase. 10 The effect of the FWOP is known to last about 60 minutes, and this is why the second stress test must be performed within this period. Exercise-induced IPC can trigger both the FWOP and the SWOP by an improved exercise/ischemic tolerance in patients.…”
Section: Molecular Pathway Of Ipcmentioning
confidence: 99%
See 1 more Smart Citation